Impact of Hypertension and Cardiovascular Diseases to Immune Response in COVID-19 Vaccination: A Systematic Review - Fahmita, Karin Dhia; Soegiarto, Gatot; Wulandari, Laksmi; Purnomosari, Dewajani (Institute of Topical Disease Universitas Airlangga, 2023)
To determine impact of hypertension and cardiovascular diseases towards effectivity and safety of COVID-19 vaccination. Systematic review based on PRISMA statement was done. Searching was conducted in PubMed, ScienceDirect, Scopus, and ProQuest and resulting in 6 studies involving 4,053 participants which deemed on good quality according to Joanna Briggs Institute tools for critical appraisal. After thorough analysis, we found that two out of four studies assessing mRNA-based vaccine found out that hypertension lower antibody response significantly. Two out of two studies assessing inactivated virus vaccine shown that hypertensive patients tend to have lower antibody titers compared to control. One of studies mentioned above found that antibody titer was not different between populations with cardiovascular diseases and control.Hypertension lessened response to COVID-19 vaccination regardless of vaccine type used. However, lack of studies on cardiovascular disease suggested that more studies should be conducted, along with hypertension, in-order to make meta-analysis possible to provide better evidence.